2017
DOI: 10.1016/j.cplett.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Stacking with the unnatural DNA base 6-ethynylpyridone

Abstract: It was previously reported that the incorporation of 6-ethynylpyridone (E) into a DNA duplex (replacing T in a T:A base pair) leads to DNA duplexes that are more stable than the T:Acontaining duplexes. DFT calculations at the M06-2X/6-31+G(d) and BLYP-D3/6-31+G(d) levels on various base pairs, stacked bases and stacked base pairs in continuum solvation water suggest that the observed increased stability of E:A-containing duplexes is due to the combined effects of stronger base pairing and enhanced stacking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The structure obtained for J was in agreement with the X-ray crystal structure, showing a coplanar arrangement of all parts of the aglycone, suitable for extensive stacking interactions, as well as the properly positioned ethynyl group for interacting with the H2-region of adenine. [24,48] Insight into the high reactivity of J in Michael-type addition reactions were obtained from calculated LUMO energies. Figure 6B shows that both J and E have large enough atom coefficients at the distal carbon of the ethynyl group for HOMO-LUMO interactions in the transition state of the addition of a soft nucleophile.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The structure obtained for J was in agreement with the X-ray crystal structure, showing a coplanar arrangement of all parts of the aglycone, suitable for extensive stacking interactions, as well as the properly positioned ethynyl group for interacting with the H2-region of adenine. [24,48] Insight into the high reactivity of J in Michael-type addition reactions were obtained from calculated LUMO energies. Figure 6B shows that both J and E have large enough atom coefficients at the distal carbon of the ethynyl group for HOMO-LUMO interactions in the transition state of the addition of a soft nucleophile.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Similar studies have recently been carried out to study the stability of canonical and non-canonical DNA base pairs. [34][35][36][37] In recent years some systematic studies were developed to rationalize and understand the relationship between the crystal structures and the NMR chemical shift tensors. 8,38 There has also been published the implementation of a new method for the evaluation of NMR chemical shifts of large biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have recently been carried out to study the stability of canonical and non-canonical DNA base pairs. 34–37…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent theoretical study, based on quantum chemistry and focusing on H-bonding, indicated that the energetic stability of the A:E pair is intermediate between those of a A:T and a G:C base pair [19] . Later on, a dispersion corrected DFT study addressed the impact of stacking interactions between E and the neighboring bases, showing a strengthening in the stacking of the A:E base pair as compared to the canonical base pairs [20] . Taken together, results of such calculations explain the increased stability of duplexes incorporating the non-natural E base facing a natural A.…”
Section: Introductionmentioning
confidence: 99%